Pengaruh Brand Image dan Word of Mouth (WOM) yang Dimediasi oleh Perceived Value terhadap Keputusan Pembelian Orang Tua Siswa di Sekolah Cendekia Harapan Badung Bali - I Gede Sindy Artha Wiguna; Saparso Saparso; Lidia Sandra (Journal on Education, 2024)
This research aims to investigate the influence of brand image and word of mouth (WOM) mediated by perceived value on the purchasing decisions of parents of students at Cendekia Harapan School in Badung, Bali. The research methodology employs a quantitative approach, distributing questionnaires to a sample of parents. The study sample consists of 158 respondents, including parents of students from kindergarten, elementary, middle, and high school levels at Cendekia Harapan School.The analysis technique used is SEM-PLS (Structural Equation Model-Partial Least Square) with SmartPLS software version 3.3.2. The results of the multiple linear regression analysis indicate that parents' purchasing decisions (PD) are not simultaneously influenced by brand image (BI) at 1.16, indicating a small impact of brand image on parents' purchasing decisions. Parents' decisions are influenced by word of mouth (WOM) at 4.12, signifying a significant impact of word of mouth on parents' purchasing decisions. Perceived value is influenced by brand image (BI) at 5.70, indicating a substantial influence of brand image on perceived value. Perceived value is influenced by word of mouth (WOM) at 6.93, emphasizing the considerable impact of word of mouth on perceived value. Parents' decisions are influenced by perceived value (PV) at 3.68, signifying a significant impact of perceived value on parents' decisions. Brand image and perceived value have a positive relationship with parents' decisions. The higher the brand image and perceived value, the higher the parents' decisions. Word of mouth (WOM) and perceived value also have a positive relationship with parents' decisions. The higher the word of mouth (WOM) and perceived value, the higher the parents' decisions.